2022
DOI: 10.1186/s12877-022-03641-z
|View full text |Cite
|
Sign up to set email alerts
|

The postoperative prognosis of older intertrochanteric fracture patients as evaluated by the Chang reduction quality criteria

Abstract: Objective The aim of this study was to investigate the relationship between the Chang reduction quality criteria (CRQC) and the outcome of intertrochanteric fractures in older adults according to follow-up time. Methods This was a retrospective analysis of 389 older adult patients with intertrochanteric fractures treated surgically from January 2019 to June 2021, including 130 males and 259 females aged 84.6 (77.5–89.7) years. Patient survival was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Meanwhile, the BRQC uses a general description, which does not differentiate between the conditions of poor alignment only in anteroposterior views, poor alignment in only lateral views, and poor alignment in both anteroposterior and lateral views, as these conditions are all grouped under the term "poor alignment." 22,29,59 Moreover, in the displacement description, the CRQC adopts expressions such as "1 or 0.5 cortical thickness." This not only provides practical means for surgeons to conduct evaluation visually, eliminating the need for measurement tools, but also underscores the buttress function of the anteromedial cortex in maintaining stability 22,59,60 .…”
Section: What Is New In Experimental Studies On Amcs?mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the BRQC uses a general description, which does not differentiate between the conditions of poor alignment only in anteroposterior views, poor alignment in only lateral views, and poor alignment in both anteroposterior and lateral views, as these conditions are all grouped under the term "poor alignment." 22,29,59 Moreover, in the displacement description, the CRQC adopts expressions such as "1 or 0.5 cortical thickness." This not only provides practical means for surgeons to conduct evaluation visually, eliminating the need for measurement tools, but also underscores the buttress function of the anteromedial cortex in maintaining stability 22,59,60 .…”
Section: What Is New In Experimental Studies On Amcs?mentioning
confidence: 99%
“…22,29,59 Moreover, in the displacement description, the CRQC adopts expressions such as "1 or 0.5 cortical thickness." This not only provides practical means for surgeons to conduct evaluation visually, eliminating the need for measurement tools, but also underscores the buttress function of the anteromedial cortex in maintaining stability 22,59,60 . In contrast, the BRQC uses a 4-mm benchmark to describe displacement, requiring the use of measuring instruments for accurate appraisal and not engaging the surgeon's attention toward the anteromedial cortex 55 .…”
Section: What Is New In Experimental Studies On Amcs?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have indicated the correlation between fracture reduction quality and the postoperative survival of elderly patients with pertrochanteric fractures. He et al ( 28 ) found that compared with patients with an excellent reduction, those with an acceptable reduction had a 1.1-fold increase in mortality at the 1-year follow-up, whereas those with a poor reduction had a 13.8-fold increase in mortality. A study including 329 patients revealed that there appeared to be a correlation between fracture reduction and postoperative survival of geriatric hip fracture patients at 1 year ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the definition of anteromedial cortical support (buttress) in the most cited article, 2 the reduction illustrated in Figure 7B should be classified as negative medial cortical support (NMCS), which is inadequate. Here is the definition 2-4 of NMCS: the medial cortex of the femoral head–neck fragment (M-HN) is lateral to the medial cortex of the femoral shaft (M-FS), regardless of the displacement. We took the liberty to mark Figure 7B with red lines to highlight the NMCS (Figure L1). Even if there was a little contact between M-HN and M-FS, the cortical support is very likely to displace after secondary interfragmentary movement (Figure 7D).…”
mentioning
confidence: 99%